The Effect of Service Quality on Employee Performance at the UPT Revenue Office Manokwari - Balia, Nikolina; Yertas, Maria; Ratag, Heidy Oktariany (Research Horizon, 2025)
Employee performance plays a vital role in determining organizational success, especially in public service institutions where effectiveness and service delivery directly influence public satisfaction. This study aims to analyze the influence of service quality on employee performance. The research applies a quantitative approach with a saturated sampling technique, involving all 45 civil servants as respondents. Primary data were collected through a structured questionnaire, and statistical analysis was performed using SPSS version 25. The analysis included validity and reliability tests, classical assumption testing, and simple linear regression supported by t-tests and coefficient of determination (R²) analysis. The findings reveal that service quality has a significant positive effect on employee performance, with the R² value showing that 48.1% of the variation in performance is explained by service quality. The results highlight that improving service quality can effectively enhance employee productivity and accountability. Therefore, public institutions should strengthen their service-oriented culture and management practices to optimize employee performance and ensure better public service outcomes.